[Infestation with the tapeworm Diphyllobothrium latum after eating raw fish] - Van Doorn, H; van Vugt, M; Wetsteyn, J; van Gool, T (2005)
A 31-year-old man with no relevant medical history encountered a white, ribbon-shaped object, 15 cm long and approximately 1 cm wide, in his faeces. It turned out to be Diphyllobothrium latum, a tapeworm that has fish as the intermediate host. The patient had eaten raw fish and shellfish during a holiday in Brazil 5 months before. He recovered after a single dose of praziquantel.